ON DEFERRED f-STATISTICAL BOUNDEDNESS - Temizsu, Fatih; Et, Mikail (Inst Applied Mathematics, 2023)
In the present paper, using deferred f-density we introduce the concept of deferred f-statistical boundedness. Along with some inclusion theorems, we present a structure theorem and a decomposition theorem and compute the a-, /3- and 7-duals of S(b)fp,q. Moreover, deferred f-statistical boundedness is compared in terms of different pairs of ?p, q? and modulus functions f and g.
Keywords: statistical boundedness; statistical convergence; modulus function; deferred mean